Effects of playing 1 vs 3 matches in a one-week period on physical performance in young soccer players - Jose Luis Hernández-Davo; Víctor Moreno Pérez; Pedro Moreno Navarro (Termedia Publishing House, 2021)
The aim of this study was to analyse the effects of playing 1 vs 3 matches in a one‑week period on physical performance in young soccer players. Twelve youth soccer players completed a battery of physical tests (countermovement jump [CMJ], 25 m sprint, 5-0-5 agility test, ankle dorsiflexion range of motion [AD ROM]) 72 h after a match. These tests were performed on two different occasions: during a week with 1 competitive match, and during a week in which 3 matches were played. Three matches in a week caused from most likely to very likely impairments in CMJ (ES = 0.81), the 5-0-5 agility test (ES = 1.03), and in AD ROM (ES = 0.46-0.63) compared with the 1 match in a week. For the 25 m sprint test, performance impairments were found in the split times for 10-15 m (ES = 0.72), 15-20 m (ES = 0.52) and 20-25 m (ES = 0.90) compared with 1 match in a week. Jumping, sprinting, change of direction (COD) performance and AD ROM are significantly affected during congested calendars in young soccer players. The monitoring of these variables is a useful tool to assess players' recovery and may help in determining players' readiness for the next matches.